Sattā, saṃskr̥ti, aura dalita saundaryaśāstra - Baṛatyā, Sūraja (Bhāratīya Dalita Adhyayana Saṃsthāna ke lie Anāmikā Pabliśarsa eṇḍa Ḍisṭrībyūṭarsa, 2010)
Study of the social conditions of Dalits, development of dalit consciousness, and aesthetics values in Hindi dalit literature.